SEIZING LIBERTY IN THE NOVEL THE UNDERGROUND RAILROAD (2016) BY COLSON WHITEHEAD - Tania Musmita; Kurnia Ningsih; An Fauzia Rozani Syafei (English Language and Literature, 2018)
The purpose of this analysis is to expose the issue about seizing liberty which is done by a slave in America and to know the contribution of the plot, setting, and character in revealing the issue of seizing liberty. This analysis is related to the psychoanalysis theory developed by Sigmund Freud and the concept of self-awareness by Crisp and Turner that are supported by the text and context based interpretation. The result of this analysis shows the efforts of a young slave woman to get free from slavery that can be seen from taking opportunities smartly and enhancing curiosity.